2012
DOI: 10.1007/128_2012_379
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbenes in FLP Chemistry

Abstract: The use of N-heterocyclic carbenes (NHCs) for the design and construction of frustrated Lewis pairs (FLPs) is outlined in this review. Stable carbene-borane adducts are briefly discussed, followed by a detailed survey of the reactivity of NHCs, in particular Arduengo-type imidazolin-2-ylidenes, towards B(C6F5)3. Structural and electronic NHC modification by variation of substituents and ring-size affords either stable normal adducts or FLPs, which undergo manifold deactivation reactions in the absence of subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 122 publications
0
28
0
Order By: Relevance
“…Instead, these compounds can act as bases or nucleophiles, with hydroboration of ketones occurring only in the presence of an additional Lewis or Brønsted acid. The combination of sterically encumbered NHCs and bulky, electrophilic boranes such as B(C 6 F 5 ) 3 does not lead to adducts but rather to frustrated Lewis pairs, which are capable of splitting hydrogen and other small molecules 73 .…”
Section: Coordination Of Nhcs To P-block Elementsmentioning
confidence: 99%
“…Instead, these compounds can act as bases or nucleophiles, with hydroboration of ketones occurring only in the presence of an additional Lewis or Brønsted acid. The combination of sterically encumbered NHCs and bulky, electrophilic boranes such as B(C 6 F 5 ) 3 does not lead to adducts but rather to frustrated Lewis pairs, which are capable of splitting hydrogen and other small molecules 73 .…”
Section: Coordination Of Nhcs To P-block Elementsmentioning
confidence: 99%
“…Thus far, the hydrogenation of unsaturated compounds with an NHC-based FLP system has been considered to be very challenging owing to the high proton affinity of NHCs. [2f] Our results show that NHC-based FLPs can indeed be employed for the hydrogenation of unsaturated compounds under appropriate reaction conditions.…”
mentioning
confidence: 93%
“…Pioneering reports by Stephan et al[10] and Tamm et al[11] disclosed that NHCs bearing N - t Bu groups reacted with B(C 6 F 5 ) 3 to give FLPs; however, the reported NHC-based FLPs easily lost their activity through a rearrangement to abnormal carbene–borane adducts or decomposition, thereby significantly limiting their utility. [2f] An intriguing progress has recently been reported by Tamm and co-workers, who found that the treatment of 1,3-di- tert -butylimidazolin-2-ylidene (I t Bu) with tris[3,5-bis(trifluoromethyl)phenyl]borane, B(XyF 6 ) 3 , resulted in complexation to give [I t Bu–B(XyF 6 ) 3 ], which reacted with 0.5 equivalents of H 2 at room temperature to give [I t Bu–H][(XyF 6 ) 3 B–H–B(XyF 6 ) 3 ] along with the loss of one I t Bu. [7a] Herein, we designed a novel NHC keeping the following considerations in mind (Figure 1): 1) The substituent on one of the nitrogen atoms should include both large (R L ) and small (R S ) units on the connecting atom (R C ); 2) drastic changes in the spatial environment surrounding the carbene center should be induced by rotation around the N–R C bond to permit for the formation of both CLA and FLP species; and 3) the interconversion between the CLA and the FLP should be brought about by external stimuli.…”
mentioning
confidence: 99%
“…In contrast, the more severely congested SItBu adducts 3 and 4 are more reactive: this is best exemplified by the fast reaction of (SItBu)GaMe 3 (3) with H 2 at room temperature to afford the corresponding aminal product, the mechanism of which is currently being studied. Such an FLP reactivity constitutes the first instance of a H 2 activation involving GaMe 3 , and further exemplifies the usefulness of bulky NHC ligands in FLP chemistry [30]. Adduct 3 was also found to mediate the ROP of rac-lactide at room temperature to afford cyclic PLA.…”
Section: Discussionmentioning
confidence: 58%